ANALISIS MOTIVASI DAN MINAT WISATAWAN MENGUNJUNGI WISATA DARK TOURISM GUNUNG MERAPI - Effendy, Graciela Meira; Rahayu, Siti; Trisnawati, Juliani Dyah (STKIP Persada Khatulistiwa Sintang, 2025)
Dark tourism, involve visiting sites linked with tragedy or death, has gained significant academic and practical interest. This study investigates the factors influencing tourists’ intentions to visit Mount Merapi, a dark tourism destination in Indonesia, using the Theory of Planned Behavior (TPB). It explores the impact of motivations such as dark experience, engaging entertainment, unique learning experience, and casual interest on attitudes and subjective norms. A quantitative approach was employed, with data collected from 300 respondents through online surveys. Results reveal that unique learning experiences and casual interest significantly influence attitudes and perceptions, while dark experience and engaging entertainment show limited effects. Tourists’ attitudes and subjective norms significantly shape their intentions to visit. The findings suggest that promoting educational and experiential elements can enhance Mount Merapi’s attractiveness. Recommendations include designing programs that offer unique learning experiences and fostering positive perceptions to engage more visitors.